The Role of Employee Involvement Mediation: The Impact of Professionalism and Self-Efficacy on Employee Work Loyalty in Bapas Class II Madiun - Julaeha Evi Susanti; Nursaid Nursaid; Budi Santoso (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of professionalism and self-efficacy on employee job loyalty with employee involvement as an intervening variable in the Class II Madiun Correctional Center (Bapas). The background of this research departs from the importance of building employee work loyalty through increasing professionalism and self-efficacy which has an impact on job engagement. This study uses a quantitative approach with a path analysis method. The research population is all employees of Bapas Class II Madiun, with sampling using census techniques. Data was obtained through the distribution of questionnaires that were tested for validity and reliability, then analyzed using the help of statistical programs. The findings of this study confirm that employee involvement has an important role as a link between professionalism and self-efficacy and work loyalty. Employees who are professional, confident, and fully engaged in their work tend to have high loyalty to the institution. Therefore, Bapas Class II Madiun needs to strengthen the strategy of developing professionalism and self-efficacy of employees in order to create sustainable work involvement and loyalty